PENGEMBANGAN DESAIN KANTOR KEPALA DESA BERBASIS DIGITAL DI DESA SEI ROTAN, DELI SERDANG - Ananda, Ananda; Pane, Danang Putra; Eka Putra; Rahmadhani Fitri (Arsil Media, 2024)
The purpose of this community service is to develop a digital-based Village Head office design. This activity was carried out in Sei Rotan Village, Percut Sei Tuan District, Deli Serdang Regency. This activity took place over several days with the main focus on the digitization program and renovation of the design of the Sei Rotan Village Head Office. This activity supports the improvement of public services through the utilization of local potential both in terms of human resources and natural resources. The method of implementing activities uses a participatory approach, with work programs including site observation, legal socialization, school teaching, posyandu implementation, as well as training and digital design of village offices. The results of the activities show the enthusiasm and active participation of the community, and the implementation of all programs according to plan. This service activity makes a real contribution to village development and is a collaborative learning experience for implementers in applying knowledge in the community.